The Relationship between Adolescent Girls' Lifestyle and the Incidence of Anemia in High School Students in Cirebon City - Anggie Puspitasari; Handayani, Oktia Woro Kasmini; Indarjo, Sofwan (Universitas Negeri Semarang, 2024)
Anemia is still one of the health problems in society, especially adolescent girls. The prevalence of anemia in adolescent girls in Cirebon City in 2023 was 36.6%. This study aims to determine the relationship between the lifestyle of adolescent girls and the incidence of anemia in high school students in Cirebon City. The method used in this study is observational analytic using a cross-sectional design. The sample used in this study was 116 adolescent girls. Data collection was carried out by means of structured interviews using questionnaires and checking Hb levels using auto check. Data analysis used includes univariate and bivariate analysis using the chi-square test and multivariate analysis using the logistic regression test. This study shows the results of a significant relationship between dietary patterns including energy consumption p = (0.001), protein consumption p = (0.009), iron consumption p = (0.001), rest patterns p (0.010) with the incidence of anemia and there is no significant relationship between physical activity patterns p = (0.331) with the incidence of anemia. Logistic regression test in multivariate analysis showed that the most influential factor on anemia was the energy consumption diet with OR 7.305. From the results of the study, it can be concluded that there is a significant relationship between diet including energy, protein and iron consumption and rest patterns with the incidence of anemia and the most influential factor on the incidence of anemia is energy consumption.